2005
DOI: 10.1186/1475-9276-4-2
|View full text |Cite
|
Sign up to set email alerts
|

The burden of non communicable diseases in developing countries

Abstract: Background: By the dawn of the third millennium, non communicable diseases are sweeping the entire globe, with an increasing trend in developing countries where, the transition imposes more constraints to deal with the double burden of infective and non-infective diseases in a poor environment characterised by ill-health systems. By 2020, it is predicted that these diseases will be causing seven out of every 10 deaths in developing countries. Many of the non communicable diseases can be prevented by tackling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
414
2
14

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 602 publications
(440 citation statements)
references
References 13 publications
10
414
2
14
Order By: Relevance
“…In developing countries, attention is being paid to CVD, diabetes and cancer, but obesity is somewhat neglected in national and international health policies. [23]. This is partly due to the fact that this condition is not generally recognized or classified as a disease.…”
Section: Discussionmentioning
confidence: 99%
“…In developing countries, attention is being paid to CVD, diabetes and cancer, but obesity is somewhat neglected in national and international health policies. [23]. This is partly due to the fact that this condition is not generally recognized or classified as a disease.…”
Section: Discussionmentioning
confidence: 99%
“…The number of diabetic patients is estimated to increase from 20.8 million in 2000 to 42.3 million in 20304. It is reported that China has overtaken India, and has become the top country with the highest number of people with diabetes for 92.4 million adults affected5, 6.…”
Section: Introductionmentioning
confidence: 99%
“…With communicable diseases still prevalent, this imposes a double-burden of disease in countries with limited resources and ill-equipped health systems (2) . An unhealthy diet, including insufficient consumption of fruit and vegetables is one of four main behavioural risk factors in the development of NCDs.…”
mentioning
confidence: 99%